2021
DOI: 10.1038/s41698-021-00182-3
|View full text |Cite
|
Sign up to set email alerts
|

A multi-omics study links TNS3 and SEPT7 to long-term former smoking NSCLC survival

Abstract: The genetic architecture of non-small cell lung cancer (NSCLC) is relevant to smoking status. However, the genetic contribution of long-term smoking cessation to the prognosis of NSCLC patients remains largely unknown. We conducted a genome-wide association study primarily on the prognosis of 1299 NSCLC patients of long-term former smokers from independent discovery (n = 566) and validation (n = 733) sets, and used in-silico function prediction and multi-omics analysis to identify single nucleotide polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Gene–environment and gene–gene interactions provided additional insights into the biological mechanisms of complex diseases [ 31 33 ]. In our previous study [ 34 ], we explored epigenome-wide gene–age interaction and significantly improved the accuracy of prognostic prediction model of oral squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Gene–environment and gene–gene interactions provided additional insights into the biological mechanisms of complex diseases [ 31 33 ]. In our previous study [ 34 ], we explored epigenome-wide gene–age interaction and significantly improved the accuracy of prognostic prediction model of oral squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…We found that carriers of two polymorphic SEPTIN7 rs3801339 alleles had shorter PFS from diagnosis, even after adjusting for clinical factors. Septin 7 is a GTP-binding protein that plays an important role in various cellular processes [ 14 , 33 ]. Its binding to the CALB2 promoter region resulted in decreased calretinin expression in MM cell lines [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that the appearance of this novel (non-adenoma) tumor cells is caused by Kras activation combined with genetic instability caused by the loss of Septin7. Interestingly, a recent multi-omics study correlated low SEPTIN7 expression levels and an intronic single-nucleotide polymorphism in the SEPTIN7 gene with higher survival rates for long-term former smoking lung cancer patients ( Shen et al, 2021 ). While the presence of Septin7 seems indispensable for oncogenic Ras-induced lung-adenocarcinoma formation, further investigations in the Septin7 conditional knockout model is necessary to completely understand the role of septins in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%